ANALISIS PELAKSANAAN PENYUSUNAN LAPORAN KEUANGAN BADAN USAHA MILIK DESA PADA KABUPATEN BELITUNG TIMUR - siswanto, siswanto; Iskandar, Iskandar; kodirin, kodirin (Universitas Muhammadiyah Palembang, 2023)
This research aims to determine the process of preparing financial reports for Village-Owned Enterprises in Belitung Timur Regency. This research was conducted on 5 village-owned enterprises in Belitung Timur Regency. The research method is qualitative with a case study approach related to the process of preparing financial reports carried out by village-owned enterprises in 2022 and 2023 as well as looking at sample data from other village-owned enterprises financial reports. The research results show that village-owned enterprises financial reports in Belitung Timur Regency have generally not been prepared in accordance with applicable standards. In 2023, Belitung Timur Regency village-owned enterprises will have prepared financial reports using an application, but there are still several errors that occur, this is because the education process for village-owned enterprises managers is still ongoing. This research offers several solutions that can be implemented, including the regional government issuing regulations requiring village-owned enterprisesto prepare financial reports according to standards, and holding training for village-owned enterprises managers.